Analysis of Readiness for the Implementation of HMIS Khanza in Sultan Imanuddin Pangkalan Bun Hospital - Fachruddin; Indasah; Ratna Wardani (Journal Of Nursing Practice, 2025)
Background: Information technology has become an important part in various aspects of life, including in the health sector. In health service facilities, information technology is useful for facilitating complex health data management processes. Purpose: This research was conducted to explore the readiness to implement HMIS KHANZA at Sultan Imanuddin Pangkalan Bun Regional Hospital. Methods: The research was conducted qualitatively with a case study approach. The informants of this research were the heads of inpatient rooms totaling 13 people. This study examines four themes including content (what has changed), process (how to implement change), context (the environment in which change occurs), Individual (characteristics of individuals who are asked to change). Results: The implementation of HMIS at Sultan Imanuddin Pangkalan Bun Hospital has had a positive impact by increasing operational efficiency, benefits for patients, and structured data management for performance analysis. Although initial adaptation may be difficult, full support from health personnel and management, training, and overcoming technical and psychological challenges are key to successful HMIS implementation. Conclusion: The implementation of HMIS has shown a positive contribution to improving hospital operational efficiency, inter-departmental coordination, and the quality of patient services.